2014
DOI: 10.18294/sc.2014.395
|View full text |Cite
|
Sign up to set email alerts
|

Género y trayectorias profesionales de las médicas de familia en Andalucía, España, a comienzos del siglo XXI

Abstract: rESuMEN el objetivo de este trabajo es estudiar, desde una perspectiva feminista, la diversidad y homogeneidad en las trayectorias profesionales de las médicas de familia que ejercían en Andalucía a comienzos del siglo XXI, a través del análisis de los significados que ellas mismas confieren a su desarrollo profesional y de la influencia de los factores personales, familiares y laborales. realizamos un estudio cualitativo con seis grupos de discusión. Participaron 32 médicas de familia que se encontraban traba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
0
2
0
9
Order By: Relevance
“…One gendered theme identified is that women in academic medicine in the U.S. face a number of barriers to career advancement, including the hierarchical structure of academic medicine, constraints of traditional gender roles, sexism from colleagues and superiors, and lack of effective mentors [14, 15]. Another study, from Spain, found that most women physicians did not plan for professional goals and/or intertwined them with family needs, although goal planning and professional development were more common among women who were health care center directors [26]. A study from the U.K. among hospital-based specialists (“consultants”) that used both interviews and observations found a number of gender-related differences-for example, female consultants tended to be less dominating and more nurturing and conversational with patients, but described higher levels of stress regarding work-life balance and gender discrimination from colleagues and lack of support from nursing staff [27].…”
Section: Introductionmentioning
confidence: 99%
“…One gendered theme identified is that women in academic medicine in the U.S. face a number of barriers to career advancement, including the hierarchical structure of academic medicine, constraints of traditional gender roles, sexism from colleagues and superiors, and lack of effective mentors [14, 15]. Another study, from Spain, found that most women physicians did not plan for professional goals and/or intertwined them with family needs, although goal planning and professional development were more common among women who were health care center directors [26]. A study from the U.K. among hospital-based specialists (“consultants”) that used both interviews and observations found a number of gender-related differences-for example, female consultants tended to be less dominating and more nurturing and conversational with patients, but described higher levels of stress regarding work-life balance and gender discrimination from colleagues and lack of support from nursing staff [27].…”
Section: Introductionmentioning
confidence: 99%
“…Los indicadores académicos en el caso de Medicina fueron de los mejores de los títulos de grado del sistema universitario español en el que se observó una clara correlación entre los estudiantes de medicina, que accedieron con la nota más alta, 11,97 y obtuvieron en su expediente académico universitario la segunda mejor nota por ámbito 7,42 (25). Esto también se manifestó en la tasa de rendimiento (créditos superados frente a matriculados) que se situó en el 87,4% en el curso 2011-2012 (25) y del 88,5% en el curso 2012-2013 a nivel nacional (26). Por otro lado, los datos de este estudio mostraron que el 74% de los estudiantes de medicina finalizaron sus estudios con una edad menor o igual a 24 años por lo que cabe esperar que invirtieran exclusivamente los 6 años de duración del grado académico.…”
Section: Discussionunclassified
“…Outros estudos já demonstraram que a maternidade é um fator que impacta na carreira de médicas de forma desigual em relação à carreira de homens (36)(37)(38)(39).…”
Section: Discussionunclassified
“…A responsabilização pelo cuidado naturalizado como uma prática feminina atravessa heranças familiares e culturais e se torna um obstáculo permanente, com a divisão desigual de tarefas domésticas e no cuidado com os filhos (38,40). Existe o reconhecimento de que cuidar dos filhos seja em parte uma tarefa com diferenças generificadas fisiologicamente.…”
Section: Discussionunclassified
See 1 more Smart Citation